Old-age financial protection in Malaysia: Challenges and options - Robert Holzmann (Institute for the Study of Labor (IZA), 2015)
This policy paper presents key findings and suggestions on Malaysia's old-age financial protection system within the context of the country's broader social security framework. The trademark policy approach focusing on job creation instead of expanding social security programs served the country well to move it quickly to a high-middle income level. But to join the club of high-income countries in a sustainable manner may require the country to review its approach to social security, including the way old-age income support is provided, and to address the main current weaknesses: fragmentation across economic sectors, lack of an enabling political environment, incomplete benefit coverage, low mandated savings level, and inadequate disbursement options given the challenges of projected population aging and socioeconomic shifts. To address the old-age financial protection challenge, the paper outlines two key options for Malaysia's Employees Provident Fund, the country's central pension pillar: (i) moving from a mere retirement savings investment fund to a fully-fledged pension fund that offers some minimum annuities; or (ii) more radically, moving the benefits toward a Non-Financial Defined Contribution scheme with the fund's resources used as its major reserve fund. Whatever approach is considered, the reform discourse would benefit from changes in the overall governance structure of social security and from a comprehensive research agenda that offers an evidence based decision making.
Keywords: H55; O16; J14; 330; employees provident fund; social security; reform options; annuities